2013
DOI: 10.1016/j.jacc.2012.09.065
|View full text |Cite
|
Sign up to set email alerts
|

VERIFY (VERification of Instantaneous Wave-Free Ratio and Fractional Flow Reserve for the Assessment of Coronary Artery Stenosis Severity in EverydaY Practice)

Abstract: iFR correlates weakly with FFR and is not independent of hyperemia. iFR cannot be recommended for clinical decision making in patients with coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(126 citation statements)
references
References 22 publications
7
110
0
3
Order By: Relevance
“…Nonetheless, encoding 3D sub-volumes of the LV myocardium could be beneficial because the myocardium is a 3D object and extracting features from its volumetric sub-regions could capture useful information that may have not been captured in the 2D encoding. Several studies investigated the reproducibility and the variability of repeated FFR measurements (Ntalianis et al, 2010;Berry et al, 2013;Petraco et al, 2013;Johnson et al, 2014). These studies reported different values (range 3% to 5%) for the standard deviation of the differences in repeated FFR measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, encoding 3D sub-volumes of the LV myocardium could be beneficial because the myocardium is a 3D object and extracting features from its volumetric sub-regions could capture useful information that may have not been captured in the 2D encoding. Several studies investigated the reproducibility and the variability of repeated FFR measurements (Ntalianis et al, 2010;Berry et al, 2013;Petraco et al, 2013;Johnson et al, 2014). These studies reported different values (range 3% to 5%) for the standard deviation of the differences in repeated FFR measurements.…”
Section: Discussionmentioning
confidence: 99%
“…13 Third, FFR measurements are extremely reproducible, unmatched by any other methodology in cardiology (Figure 2). 9 Fourth, the concept of FFR can be extended to calculate separately myocardial coronary, and collateral perfusion (to be discussed later). 8 Fifth, by performing a so-called hyperemic pressurepullback recording, detailed spatial information can be obtained about the distribution of all abnormalities along the coronary tree.…”
Section: Concept and Features Of Ffrmentioning
confidence: 99%
“…9,31 It has been well documented in several recently published studies and in a large registry that, if a 95% certainty of making the right decision is requested, relying solely on iFR (and removing a hyperemic stimulus) leads to the correct decision in only 25% of all patients, whereas Pd/ Pa at rest would be reliable for that purpose in 33% of all patients ( Figure 6). 9,29,31 In the literature advocating the use of iFR, investigators suggest being satisfied with an accuracy of only 90% or, even worse, 80%. But if 80% accuracy of making the right decision to stent or not to stent is sufficient, we could rely just as well on angiography and coronary pressure measurement would never be necessary.…”
Section: Is Hyperemia Essential? a Critical Word About Resting Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADVISE study (Adenosine Vasodilator Independent Stenosis Evaluation) has shown that there is a statistically significant correlation between FFR and iFR (R = 0.91, p <0.0001), and that an iFR cut-off value of 0.9 is equivalent to an FFR value of 0.80. 33 Comparative studies between FFR and iFR, performed with the pull-back technique in coronary arteries with diffuse atherosclerotic involvement, is highly specific, and it allows reductions in the number of implanted stents, as well as a decrease in length for stents, subsequently decreasing the risk for thrombotic events. 34 The ADVISE II trial recommends that at an iFR value of <0.86, PCI should be performed, and at an iFR value of >0.94, pharmacological therapy should be initiated.…”
Section: Determination Of Instantaneous Wave-free Ratio (Ifr)mentioning
confidence: 99%